Immunity to Pathogens Taught by Specialized Human Dendritic Cell Subsets - Geginat, Jens; Nizzoli, Giulia; Paroni, Moira; Maglie, Stefano; Larghi, Paola; Pascolo, Steve; Abrignani, Sergio (Frontiers in Immunology, 2015)
Dendritic cells (DCs) are specialized antigen-presenting cells (APCs) that have a key role in immune responses because they bridge the innate and adaptive arms of the immune system. They mature upon recognition of pathogens and upregulate MHC molecules and costimulatory receptors to activate antigen-specific CD4+ and CD8+ T cells. It is now well established that DCs are not a homogeneous population but are composed of different subsets with specialized functions in immune responses to specific pathogens. Upon viral infections, plasmacytoid DCs (pDCs) rapidly produce large amounts of IFN-α, which has potent antiviral functions and activates several other immune cells. However, pDCs are not particularly potent APCs and induce the tolerogenic cytokine IL-10 in CD4+ T cells. In contrast, myeloid DCs (mDCs) are very potent APCs and possess the unique capacity to prime naive T cells and consequently to initiate a primary adaptive immune response. Different subsets of mDCs with specialized functions have been identified. In mice, CD8α+ mDCs capture antigenic material from necrotic cells, secrete high levels of IL-12, and prime Th1 and cytotoxic T-cell responses to control intracellular pathogens. Conversely, CD8α− mDCs preferentially prime CD4+ T cells and promote Th2 or Th17 differentiation. BDCA-3+ mDC2 are the human homologue of CD8α+ mDCs, since they share the expression of several key molecules, the capacity to cross-present antigens to CD8+ T-cells and to produce IFN-λ. However, although several features of the DC network are conserved between humans and mice, the expression of several toll-like receptors as well as the production of cytokines that regulate T-cell differentiation are different. Intriguingly, recent data suggest specific roles for human DC subsets in immune responses against individual pathogens. The biology of human DC subsets holds the promise to be exploitable in translational medicine, in particular for the development of vaccines against persistent infections or cancer.